Crystal structure of benzyltriphenylphosphonium chloride monohydrate - Ahmad, Jimmy; Abdul Halim, Siti Nadiah; How, Fiona Ni Foong (International Union of Crystallography, 2015)
The title compound, Ph3(PhCH2)P+ Cl-·H2O, was obtained unintentionally as the product of an attempted synthesis of a silver dithiocarbamate complex using benzyltriphenyl- phosphonium as the counter-ion. The asymmetric unit consists of a phosphonium cation and a chloride anion, and a water molecule of crystallization. In the crystal, the chloride ion is linked to the water molecule by an O—H·· ·Cl hydrogen bond. The three units are further linked via C—H·· ·Cl and C— H·· ·O hydrogen bonds and C—H··· JT interactions, forming a three-dimensional structure.